Is climatic regionalization in frame of estimated pedologic-ecological system actual in 21st century? - STŘEDOVÁ, Hana; CHUCHMA, Filip (Contributions to Geophysics and Geodesy, 2014)
Climatic variables defining climatic regions of estimated pedologic-ecologicalsystem (EPEU) were calculated based on fifty-year climatic data from 1961 to 2010. Obtainedresults were subsequently compared to intervals determining individual climaticregions defined by previous climatic data (1901–1950). In many agricultural intense areassum of air temperature and mean air temperature exceeded upper limit. In terms of precipitationit is especially noticeable in the wet (higher) altitudes. Significant volatility wasfound for probability of dry periods from April to September. The values of the moisturecertainty from April to September for the period 1961–2010 reached to several tens. Inthe final analysis, the only safe prediction is that the present and future are likely to bevery different from the past. It is necessary to take it into account for actualization ofEPEU methodology. Among the strongest arguments justifying the need of this actualizationis in particular climate development since 1901, technological progress and improvedmeasurement technology as well as automation and development of climate models coupledwith simulations of complex characteristics and estimates of future climate. It isevident that the development of climate and other factors have an enormous impact onsoil fertility. This should be also taken into consideration when fixing the official price. Itis necessary to consider the possible replacement of the existing characteristics by moresuitable (for example soil moisture balance). The findings might be summarized in fewwords: old climatic regions do not reflect actual climatic conditions.